Tuberculosis: The success tale of less explored dormant Mycobacterium tuberculosis - Verma, Akanksha; Ghoshal, Antara; Dwivedi, Ved Prakash; Bhaskar, Ashima (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium tuberculosis (M.tb) is an intracellular pathogen that predominantly affects the alveolar macrophages in the respiratory tract. Upon infection, the activation of TLR2 and TLR4- mediated signaling pathways leads to lysosomal degradation of the bacteria. However, bacterium counteracts the host immune cells and utilizes them as a cellular niche for its survival. One distinctive mechanism of M.tb to limit the host stress responses such as hypoxia and nutrient starvation is induction of dormancy. As the environmental conditions become favorable, the bacteria resuscitate, resulting in a relapse of clinical symptoms. Different bacterial proteins play a critical role in maintaining the state of dormancy and resuscitation, namely, DevR (DosS), Hrp1, DATIN and RpfA-D, RipA, etc., respectively. Existing knowledge regarding the key proteins associated with dormancy and resuscitation can be employed to develop novel therapies. In this review we aim to highlight the current knowledge of bacterial progression from dormancy to resuscitation and the gaps in understanding the transition from dormant to active state. We have also focused on elucidating a few therapeutic strategies employed to prevent M.tb resuscitation.